The Impact of Vortex Formation Due to the Operational Dam Condition: A Review - Azman A.; Zahari N.M.; Zawawi M.H.; Mansor M.H.; Ng F.C.; Abas A.; Nurhikmah F.; Aziz N.A. (IOP Publishing Ltd, 2023)
There are various sources of energy throughout the world, renewable as well as non-renewable through which renewable energy sources are considered more environmentally friendly. Encompassed by all the sources of renewable energy, hydropower is considered the most beneficial source of energy. Proper operation of hydropower plant is very important for generating maximum energy by utilizing the available. However, formation of vortices at power intake can cause number of problems. The stronger vortices have more negative effects on the performance of hydropower plant which can also, draw debris and air into an intake causing vibration and damage to turbines. The present study addresses the vortices formation at the intake dam, several types of vortices and anti-vortex applications in order to overcome the vortex formations. Published under licence by IOP Publishing Ltd.